Form follows function in human nonverbal vocalisations. Issue 3 (4th May 2022) - Pisanski, Katarzyna; Bryant, Gregory A.; Cornec, Clément; Anikin, Andrey; Reby, David
Abstract : Until recently, human nonverbal vocalisations such as cries, laughs, screams, moans, and groans have received relatively little attention in the human behavioural sciences. Yet these vocal signals are ubiquitous in human social interactions across diverse cultures and may represent a missing link between relatively fixed nonhuman animal vocalisations and highly flexible human speech. Here, we review converging empirical evidence that the acoustic structure ("forms") of these affective vocal sounds in humans reflect their evolved biological and social "functions". Human nonverbal vocalisations thus largely parallel the form-function mapping found in the affective calls of other animals, such as play vocalisations, distress cries, and aggressive roars, pointing to a homologous nonverbal vocal communication system shared across mammals, including humans. We aim to illustrate how this form-function approach can provide a solid framework for making predictions, including about cross-species and cross-cultural universals or variations in the production and perception of nonverbal vocalisations. Despite preliminary evidence that key features of human vocalisations may indeed be universal and develop reliably across distinct cultures, including small-scale societies, we emphasise the important role of vocal control in their production among humans. Unlike most other terrestrial mammals including nonhuman primates, people can flexibly manipulate vocalisations, from conversational laughter and fake pleasure moans to exaggerated roar-like threat displays. We discuss how human vocalisations may thus represent the cradle of vocal control, a precursor of human speech articulation, providing important insight into the origins of speech. Finally, we describe how ground-breaking parametric synthesis technologies are now allowing researchers to create highly naturalistic, yet fully experimentally controlled vocal stimuli to directly test hypotheses about form and function in nonverbal vocalisations, opening the way for a new era of voice sciences.